An Orphan G Protein-Coupled Receptor, GPR1, Acts as a Coreceptor To Allow Replication of Human Immunodeficiency Virus Types 1 and 2 in Brain-Derived Cells - Shimizu, Nobuaki (American Society for Microbiology, 1999)
Twelve G protein-coupled receptors, including chemokine receptors, act as coreceptors and determinants for the cell tropisms of human immunodeficiency virus type 1 (HIV-1), HIV-2, and simian immunodeficiency virus (SIV). We isolated HIV-1 variants from T-cell-line (T)- and macrophage (M)-tropic (i.e., dualtropic) (R5-R3-X4) HIV-1 strains and also produced six HIV-1 mutants carrying single-point amino acid substitutions at the tip of the V3 region of the Env protein of HIV-1. These variants and three mutants infected brain-derived CD4-positive cells that are resistant to M-, T-, or dualtropic (R5, X4, or R5-X4) HIV-1 strains. However, a factor that determines this cell tropism has not been identified. This study shows that primary brain-derived fibroblast-like cell strains, BT-3 and BT-20/N, as well as a CD4-transduced glioma cell line, U87/CD4, which were susceptible to these HIV-1 variants and mutants and the HIV-2(ROD) strain, expressed mRNA of an orphan G protein-coupled receptor (GPCR), GPR1. When a CD4-positive cell line which was strictly resistant to infection with diverse HIV-1 and HIV-2 strains was transduced with GPR1, the cell line became susceptible to these HIV-1 variants and mutants and to an HIV-2 strain but not to T- or dualtropic HIV-1 strains, and numerous syncytia formed after infection. These results indicate that GPR1 functions as a coreceptor for the HIV-1 variants and mutants and for the HIV-2(ROD) strain in vitro.